2007
DOI: 10.1039/b616082d
|View full text |Cite
|
Sign up to set email alerts
|

Applications of and alternatives to π-electron-deficient azine organometallics in metal catalyzed cross-coupling reactions

Abstract: While the use of pi-deficient azine halides in palladium catalyzed cross-coupling reactions is common, the use of pi-electron deficient azine organometallics has been less intensively examined. In recent years, important advances have been made that are beginning to address this deficiency and need. The purpose of this tutorial review is to highlight and discuss the innovations that facilitate the synthesis of azine-containing biaryls with a focus on the pyridine structural motif. Given the number of important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(81 citation statements)
references
References 77 publications
0
80
0
1
Order By: Relevance
“…[75,98] Notably, this transformation represents a valuable alternative to the use of often unstable organometallic 2-pyridyl deriv-atives [99,100] in traditional cross-coupling reactions. [101] Intermolecular competition experiments revealed that the less nucleophilic, but more C À H acidic pronucleophiles reacted preferentially (Scheme 54). In addition, the observed intermolecular primary kinetic isotope effect (KIE) of 4.7 could not be rationalized with an S E Ar mechanism.…”
Section: Aryl Triflates Iodides Bromides and Their Derivativesmentioning
confidence: 98%
“…[75,98] Notably, this transformation represents a valuable alternative to the use of often unstable organometallic 2-pyridyl deriv-atives [99,100] in traditional cross-coupling reactions. [101] Intermolecular competition experiments revealed that the less nucleophilic, but more C À H acidic pronucleophiles reacted preferentially (Scheme 54). In addition, the observed intermolecular primary kinetic isotope effect (KIE) of 4.7 could not be rationalized with an S E Ar mechanism.…”
Section: Aryl Triflates Iodides Bromides and Their Derivativesmentioning
confidence: 98%
“…(Schema 53). [75,98] Diese Umsetzung bietet eine wertvolle Alternative zur Verwendung oftmals instabiler metallorganischer 2-Pyridylderivate, [99,100] wie sie bei herkömmlichen Kreuzkupplungen [101] zum Einsatz kommen. Intermolekulare Konkurrenzexperimente offenbarten, dass das weniger nukleophile, aber C-H-acidere Pronukleophil bevorzugt reagiert (Schema 54).…”
Section: Aryltriflate -Iodide -Bromide Und Derivateunclassified
“…2,6-Di(4-methoxylphenyl)pyridine (7 d 4,156.3,137.3,132.3,128.2,117.1,114.0,pyridine (6 e 3,149.6,136.7,135.5,128.6 (d,J = 8.6 Hz),121.9,120.1,115.5 ppm (d,J = 21.5 Hz); MS (EI): m/z (%): 173 (100) [M] + , 172 (68.0); elemental analysis calcd (%) for C 11 H 8 FN: C 76.29,H 4.66,N 8.09;found: C 76.32;H 4.64;N 8.07. 2,pyridine (7 e): White solid; m.p.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Although transition-metal-catalyzed cross-coupling reactions between organometallic electron-rich heterocycles and arylhalides have been widely used, their application has been limited to pyridine derivatives. [3,4] The reason for this is that the pyridine ring is electron deficient and the highly effective and relatively stable ortho-pyridyl organometallics have only been presented recently. [5] However, direct arylation of heterocycles has emerged as an alternative to the traditional crosscoupling reaction in past years [6] and pioneering work on the direct ortho-arylation of pyridine has made significant achievements.…”
Section: Introductionmentioning
confidence: 98%